The United States in decline - Lachmann, Richard (Political power and social theory ;, 2014)
The essays in this volume examine finance, industry and strategy both internally and on a global scale. Contributors clarify our understanding of the current state and future trajectory of the United States and the effect of decline on its citizens and the world.